The Critique of Ideological Legal Reason - Stambulski, Michał (University of Wroclaw. Faculty of Law, Administration & Economics, 2015)
This work aims to present the usefulness of the notion of ideology in the research of legal discourse. There are at least two approaches to the whole issue of the relation between law and ideology. The first refers to Marx and is useful in researching the content of law. “Young Marx’s” political ontology helps to reveal political entanglements of concrete regulations, especially those regulating private ownership. An example of such research may be the issue of “forest theft” discussed by Marx in his 1842 article. The other approach to ideology, indebted to Louis Althusser and creatively developed by Slavoj Žižek, focuses on the issue of form. The view of ideology as a material practice exposes political entanglements of the form of law (e.g. democracy, rule of law, constitution). Susan Marks’ critique of constitutionalism and democracy is an example of such an approach. To resort to the language ideological of critique, especially in the post-Soviet countries, we have to begin by legitimising our approach. In other words, we have to prove that ideology is still alive.
Keywords: dyskurs prawniczy; ideologia